Current Diagnostic and Therapeutic Approaches to Patients with Acquired von Willebrand Syndrome: A 2013 Update - Federici, Augusto B.; Budde, Ulrich; Castaman, Giancarlo; Rand, Jacob H.; Tiede, Andreas (Seminars in Thrombosis and Hemostasis, 2013)
Acquired von Willebrand syndrome (AVWS) is an acquired bleeding disorder, first reported in 1968, with clinical and laboratory features similar to inherited von Willebrand disease. This rare bleeding disorder occurs mainly in patients with underlying lymphoproliferative, cardiovascular, myeloproliferative, and immunologic disorders. In contrast to acquired hemophilia A, AVWS is rarely associated with measurable anti-von Willebrand factor inhibitors. In most instances, AVWS is identified because of bleeding complications: in fact, more than 80% of the patients with this syndrome are active bleeders. Recurrent bleeding episodes occur in approximately 20 to 33% of patients with AVWS, especially following major trauma and surgery. Because of the heterogeneous mechanisms of AVWS, more than one therapeutic approach is often required to prevent or treat acute bleedings. Remission from some forms of AVWS can be obtained when the underlying disorders are treated.
Keywords: acquired von Willebrand syndrome; inhibitors; lymphoproliferative diseases; cardiovascular diseases; thrombocythemia; autoimmune conditions